Styl polityczny Marine Le Pen. Rodzinna sukcesja - Orzechowska-Słowikowska, Daria (Civitas. Studia z filozofii polityki, 2016)
Marine Le Pen is one of the most famous and controversial individuals on the French, or perhaps European, political scene. Her opponents describe her as imperious, ruthless, often unfair and too self-confident, whereas her supporters appreciate her intelligence, effectiveness and ambition. Marine Le Pen divides public opinion like hardly any other politician in France. Malicious individuals emphasize that she graduated with honours from the best school of political leadership – the Jean-Marie Le Pen school. Marine Le Pen, however, stresses that ‘she will die as the daughter of her father’. Her goal is to ‘de-demonize’ the National Front, whose leader she became in 2011. It must be admitted that she is determined to achieve her objective. What exactly is known about the current leader of the National Front? How much of what is written in books dedicated to Marine Le Pen is truth and how much of it is fiction, created for the purpose of developing the image of a woman and a mother on the one hand and a political beast on the other? For researchers, the analysis of Marine Le Pen’s political style is a challenge. Firstly, it is difficult to operationalize the very notion of ‘political style’. Secondly, there is not much research on the her political activity or her leadership of the National Front.